Evidence for Persistent Monocyte and Immune Dysregulation After Prolonged Viral Suppression Despite Normalization of Monocyte Subsets, sCD14 and sCD163 in HIV-Infected Individuals - Anjana Yadav; Andrew V. Kossenkov; Vincent R. Knecht; Louise C. Showe; Sarah J. Ratcliffe; Luis J. Montaner; Pablo Tebas; Ronald Collman (Case Western Reserve University, 2019)
Background: People living with HIV on antiretroviral therapy (HIV/ART) experience excess non-AIDS comorbidities, and also remain at increased risk for certain infections and viral malignancies. Monocytes/macrophages are central to many of these comorbidities, and elevated plasma cytokines and immune activation during untreated infection are often incompletely reversed by ART and are also associated with comorbidities. Methods: We investigated monocyte surface markers, gene expression, and plasma cytokines in 11 HIV-infected older individuals (median 53 years) who started therapy with low CD4 counts (median 129 cells/μl), with elevated hsCRP (≥ 2mg/L) despite long-term ART (median 7.4 years), along with matched controls. Results: Frequency of monocyte subsets (based on CD14/CD16/CD163), were not different from controls, but surface expression of CD163 was increased (P = 0.021) while PD1 was decreased (P = 0.013) along with a trend for higher tissue factor (P = 0.096). As a group, HIV/ART participants had elevated plasma CCL2 (MCP-1; P = 0.0001), CXCL9 (MIG; P = 0.04), and sIL2R (P = 0.015), which were correlated, while sCD14 was not elevated. Principal component analysis of soluble markers revealed that 6/11 HIV/ART participants clustered with controls, while 5 formed a distinct group, driven by IL-10, CCL11, CXCL10, CCL2, CXCL9, and sIL2R. These individuals were significantly older than those clustering with controls. Transcriptomic analysis revealed multiple genes linked to immune functions including inflammation, immune cell development, and cell-cell signaling that were downregulated in HIV/ART monocytes and distinct from patterns in untreated subjects. Conclusions: Long-term ART-treated individuals normalize monocyte subsets but exhibit immune dysregulation involving both aberrant inflammation and monocyte dysfunction, as well as inter-individual heterogeneity, suggesting complex mechanisms linking monocytes and HIV/ART comorbidities.